2020
DOI: 10.1152/ajpendo.00157.2020
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone supplementation upregulates androgen receptor expression and translational capacity during severe energy deficit

Abstract: Testosterone supplementation during energy deficit promotes whole-body lean mass accretion, but the mechanisms underlying that effect remain unclear. To elucidate those mechanisms, skeletal muscle molecular adaptations were assessed from muscle biopsies collected before (Resting), 1 h (Post) and 6 h (Recovery) after exercise and a mixed meal (40 g protein, 1 h post-exercise) following 14 days of weight maintenance (WM) and 28 days of an exercise- and diet-induced 55% energy deficit (ED) in 50 physically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
2
16
0
1
Order By: Relevance
“…Without any counteracting stimuli (e.g., RT), attenuation of MPS ultimately leads to a negative net protein balance and, hence, to lean tissue loss (Roth et al 2021;Pasiakos et al 2013). This is supported by the data of athletes taking performance-enhancing drugs who, due to ergogenic effects on protein turnover, do not show significant lean tissue loss (Pasiakos et al 2019;de Souza et al 2018;Howard et al 2020). Although RT is widely recognized as a potent countermeasure against CR-induced alterations, lean tissue loss is also often reported (Weinheimer et al 2010).…”
Section: Intracellular Pathwaysmentioning
confidence: 93%
“…Without any counteracting stimuli (e.g., RT), attenuation of MPS ultimately leads to a negative net protein balance and, hence, to lean tissue loss (Roth et al 2021;Pasiakos et al 2013). This is supported by the data of athletes taking performance-enhancing drugs who, due to ergogenic effects on protein turnover, do not show significant lean tissue loss (Pasiakos et al 2019;de Souza et al 2018;Howard et al 2020). Although RT is widely recognized as a potent countermeasure against CR-induced alterations, lean tissue loss is also often reported (Weinheimer et al 2010).…”
Section: Intracellular Pathwaysmentioning
confidence: 93%
“…Ar interacts with DNA when it is bound by androgens such as testosterone [69, 70], and it has also been shown that testosterone levels are positively correlated with Ar gene expression [71]. Supplements of testosterone increase Ar gene expression in human studies [72, 73]. These observations are interesting in the context of published evidence showing that exposure to sevoflurane increases testosterone levels in male animals [74, 75] and that a surge of testosterone takes place during germ cell and gonadal sex differentiation [70].…”
Section: Resultsmentioning
confidence: 99%
“…ARs are not only responsible for mediating the anabolic effects of T ( 10 , 36 ), but are also critical for muscle fiber remodeling following chronic RT ( 37 , 38 ). In males, administration of T is commonly accompanied by increased intramuscular AR content ( 13 , 14 , 17 , 35 , 39 ), but no study has previously examined whether such change occur in young women. In the present study, despite raising T serum concentrations ~ fivefold above basal levels, AR protein expression remained unchanged, a somewhat unexpected finding given that basal muscle AR content is lower in women than in men ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies seeking to depict the role of mTORC1-signaling in human muscle following T provision are scarce and have provided mixed results. Howard et al., 2020 showed that weekly injections of T enanthate (200 mg) during 28-days of severe energy deficit did not alter mTORC1-signaling following exercise and protein intake in young men ( 13 ). On the other hand, Gharahdaghi and colleagues showed that biweekly T injections (Sustanon, 250 mg) in combination with resistance training potentiated exercise-induced mTORC1-signaling in old men ( 14 ).…”
Section: Introductionmentioning
confidence: 99%